The Marketing Mix And Cashless Payments As Determinants Of Purchasing Decisions Among Mobile Coffee SMES, Moderated By Islamic Business Ethics - Alfa Rizki Madhani; Muchamad Fauzi; Riska Wijayanti (Universitas Islam Darul 'ulum Lamongan, 2026)
This study aims to analyze the influence of the marketing mix (4Ps) and the adoption of cashless payments on purchasing decisions in mobile coffee shops, and to examine the role of Islamic business ethics as a moderating variable. The main problem examined is the suboptimal increase in purchasing decisions despite MSMEs adopting digital technology and modern marketing strategies. The study used a quantitative, explanatory approach, involving 100 respondents selected through purposive sampling. Data were collected through a Likert-scale questionnaire and analyzed using Structural Equation Modeling based on Partial Least Squares (SEM-PLS). The results show that the marketing mix has a positive and significant effect on purchasing decisions. Islamic business ethics also has a significant positive effect on increasing purchasing decisions by strengthening consumer trust. However, cashless payments did not significantly influence purchasing decisions, and Islamic business ethics was unable to moderate the relationship between the marketing mix and cashless payments on purchasing decisions. These findings confirm that marketing strategy and ethical values ​​play a more dominant role than technological aspects in influencing consumer behavior in mobile coffee shops